Peningkatan Minat Belajar Matematika Melalui Strategi Talking Stick Dengan Menggunakan Media Kertas Berpetak Pada Siswa Kelas IV SDN Pilangsari 2 Tahun Ajaran 2015/2016 - Wibawa, Dicky Nararia Drajat; , Drs Suwarno SH., M.Pd (2016)
Dicky Nararia Drajat Wibawa / A510120052. Increased Interest in Learning Mathematics Through Talking Stick Strategies Using Media terraced Fourth Grade Students of SDN Pilangsari 2 Academic Year 2015/2016. Thesis, Department of Primary School Teacher Education, the Faculty of Education, University of Muhammadiyah Surakarta. Februar 2016. This research applies the model of learning through talking stick strategy using paper media's puzzle that aims to: Increase miknat studying Maths grade IV SDN Pilangsari 2 of the school year 2015/2016. This type of research is a classroom action research. The research subject teachers and students in grade IV SDN Pilangsari 2 totaling 20 children. The technique of collecting data through observation, testing, documentation, and interviews. Data analysis technique used is interactive analysis starts from data reduction, data presentation and then draw conclusions. This study shows that the model of learning through talking stick strategy using paper media's puzzle can increase student interest. Model learning through talking stick strategy using paper media terraced may also increase interest in learning Mathematics. It initerlihat of pre-cycle 30% (6 students completed) then the first cycle at 50% (10 students completed) Cycle II to 95% (19 students complete). The conclusion of this study were: 1) learning model through strategic taliking stick with using paper media's puzzle can increase student interest in learning mathematics class IV SDN Pilangsari 2 of the school year 2015/2016.